2009
DOI: 10.1080/10926770903291795
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Help-Seeking Among Immigrant African Women Survivors of Partner Abuse: Listening to Women's Own Voices

Abstract: Most studies in the United States documenting immigrant women's experiences of intimate partner violence (IPV) have not included the perspectives of abused immigrant African women. This study utilized a phenomenological approach to explore help-seeking barriers and factors impacting decisions to leave an abusive relationship among 15 immigrant African women. Results from the qualitative analysis indicated that the culture of gender inequality and acceptance of gender violence were primary barriers. Selfblame, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
92
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 32 publications
9
92
0
10
Order By: Relevance
“…More recent findings by Ting and Panchanadeswaran (2009) and Ting (2010) documented barriers to help-seeking and coping strategies as perceived by 15 immigrant African women who were survivors of IPV. Ting and Panchanadeswaran (2009) found that among immigrant African women, the culture of gender inequality and acceptance of gender violence were the primary barriers to help-seeking, and additional barriers included self-blame, loyalty, concerns for children, and lack of knowledge about abuse, available services, and legal rights.…”
mentioning
confidence: 98%
“…More recent findings by Ting and Panchanadeswaran (2009) and Ting (2010) documented barriers to help-seeking and coping strategies as perceived by 15 immigrant African women who were survivors of IPV. Ting and Panchanadeswaran (2009) found that among immigrant African women, the culture of gender inequality and acceptance of gender violence were the primary barriers to help-seeking, and additional barriers included self-blame, loyalty, concerns for children, and lack of knowledge about abuse, available services, and legal rights.…”
mentioning
confidence: 98%
“…In the literature on women's responses to IPV, women's agency has largely been conceptualised in relation to two particular actions: (1) reporting the violence to formal sources (police, health and social services, the justice system, shelters) or informal sources (family, friends, neighbours) (Andersson et al, 2010;Kim & Lee, 2011), and (2) leaving the abusive relationship (Scheffer, Lindgren & Renck, 2008). In this paper we are interested in exploring women's agency and IPV in constrained social contexts: settings where violence against women is socially and/or culturally acceptable, and actions such as reporting or leaving a violent relationship are rarely, if ever, taken (Kouyoumdjian et al, 2013;Linos & Kawachi, 2012;Ting & Panchanadeswaran, 2009;Uthman, Lawoko, & Moradi, 2009). In such contexts, two of the reasons women are unlikely to report violence are because they themselves are tolerant of IPV (Rizo & Macy, 2011;Schuler & Islam, 2008;Ting & Panchanadeswaran, 2009) or because they lack knowledge about available options (Saito, Cooke, Creedy, & Chaboyer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we are interested in exploring women's agency and IPV in constrained social contexts: settings where violence against women is socially and/or culturally acceptable, and actions such as reporting or leaving a violent relationship are rarely, if ever, taken (Kouyoumdjian et al, 2013;Linos & Kawachi, 2012;Ting & Panchanadeswaran, 2009;Uthman, Lawoko, & Moradi, 2009). In such contexts, two of the reasons women are unlikely to report violence are because they themselves are tolerant of IPV (Rizo & Macy, 2011;Schuler & Islam, 2008;Ting & Panchanadeswaran, 2009) or because they lack knowledge about available options (Saito, Cooke, Creedy, & Chaboyer, 2009). Legal cynicism or mistrust of the police can also act as barriers to help-seeking from authorities (Emery, Jolley, & Wu, 2011), and the potential stigma of being an abused woman can prevent women from seeking help from family or friends (Andersson et al, 2010;Overstreet & Quinn, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Older African immigrants may not readily assimilate the host environment compared to younger immigrants for example, they may have had healthier eating practices in their countries before relocation [24]. In spite of African immigrant men and women working for a living, women don't report domestic violence because of cultural differences and financial dependence on spouses as well the need to have an intact marriage [26]. Among African immigrants who came into the US at the age of 13 or older, the risk of mood and anxiety disorders is lower than their US counterparts (OR= 0.43-Mood disorders, 0.47= anxiety disorders).…”
Section: Chronic Diseasementioning
confidence: 99%
“…These include stress, depression, mood disorders, anxiety, domestic abuse and posttraumatic stress disorder [14,26]. Refugees suffer post-traumatic stress disorder, depression and ostracism [15,27].…”
Section: Chronic Diseasementioning
confidence: 99%